2022
DOI: 10.3390/cancers14153623
|View full text |Cite
|
Sign up to set email alerts
|

Novel Germline Mutations in a Cohort of Men with Familial Prostate Cancer

Abstract: Background: Germline mutations in BRCA2 are associated with aggressive prostate cancer. Additional information regarding the clinical phenotype of germline pathogenic variants in other prostate cancer predisposition genes is required. Clinical testing has been limited by evidence, further restricting knowledge of variants that contribute to prostate cancer development. Objective: Prostate cancer patients who were first- and second-degree relatives from multi-case prostate cancer families underwent a gene panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…HOXB13 was the first gene that was shown to enhance the prostate cancer risk by up to 10 times and was linked with familial cases of PCa and early-onset disease in some [23,31,33] but not all studies [43]. Specifically, the mutant HOXB13G84E has been associated with lower-risk tumor characteristics [43], early-onset disease [33] and European origin among patients [31,33]. Other alterations have been encountered in different populations, such as G135E in Chinese men and variants A128D and F240L in Portuguese men [31].…”
Section: Brca and Non-brca Mutationsmentioning
confidence: 99%
See 3 more Smart Citations
“…HOXB13 was the first gene that was shown to enhance the prostate cancer risk by up to 10 times and was linked with familial cases of PCa and early-onset disease in some [23,31,33] but not all studies [43]. Specifically, the mutant HOXB13G84E has been associated with lower-risk tumor characteristics [43], early-onset disease [33] and European origin among patients [31,33]. Other alterations have been encountered in different populations, such as G135E in Chinese men and variants A128D and F240L in Portuguese men [31].…”
Section: Brca and Non-brca Mutationsmentioning
confidence: 99%
“…A recent study conducting genome analysis on non-BRCA-mutated PCa showed that germline ATM and CHEK2 alterations had lower penetrance than BRCA2. In addition, prostate cancer carried different genetic alterations in these genes compared to breast and ovarian cancer [43]. Germline CHEK2 mutations increase the risk for PCa development at a moderate level [23] and have been linked with aggressive or high-risk cancer [43].…”
Section: Brca and Non-brca Mutationsmentioning
confidence: 99%
See 2 more Smart Citations